Local existence and blow up of solutions to a logarithmic nonlinear wave equation with time-varying delay - CHOUCHA, Abdelbaki; OUCHENANE, Djamel (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
In this work, we are concerned with a problem of a logarithmic nonlinear wave equation with time-varying delay term. We established the local existence result and we proved a blow up result for the solution with negative initial energy under suitable conditions. This improves earlier results in the literature [11] for time-varying delay. Mathematics Subject Classification (2010): 35B05, 35B40, 35Q99, 73C99. Received 03 February 2020; Revised 21 April 2020. Published Online: 2023-03-20. Published Print: 2023-04-30